Integrated methodology for assessing the readiness of a territory for the creation of a transport cluster - K. B. Malysheva (Вестник университета)
The process of transport clustering is a tool for the regional spatial development of the country, since it contributes to the elimination of infrastructural constraints, increasing the availability and quality of the main transport infrastructure and increasing the competitiveness of the territory. The choice of a territory for the creation of a transport and logistics cluster (hereinafter - TLC) is an important stage in the development of the clustering process, but there is no methodology that assesses the conditions of the region for the creation of a TLC. The aim of the work is to develop a methodology for assessing the readiness of the territory to create a TLC. To achieve this goal, the following tasks were completed: indicators were developed that characterize the conditions for the creation of a TLC; mathematical tools of the methodology were developed; three groups of regions were identified according to the value of assessing readiness for the creation of a TLC; the methodology was tested in the regions of the Russian Federation and subjects ready to create a transport cluster were identified. As a result of the methodology approbation the regions of the Russian Federation were assessed according to the degree of readiness for transport clustering, which forms the basis for the spatial development of the territory.